2014
DOI: 10.1159/000363621
|View full text |Cite|
|
Sign up to set email alerts
|

Cognitive Profiles in Patients with Multi-Infarct Dementia: An Omani Study

Abstract: Background: Studies on neurocognitive impairment among patients presenting with multi-infarct dementia (MID) have received little attention from non-Western societies, and the Arab world is no exception. To our knowledge, this is the first study to characterize neurocognitive, affective and vegetative functioning in patients with MID in Oman. Methods: In this study, we recruited 20 Omani patients presenting with MID and age- and gender-matched controls at the outpatient clinic of the Department of Behavioral M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
(68 reference statements)
0
8
0
Order By: Relevance
“…Verbal Fluency. In the Controlled Oral Word Association Test, or Verbal Fluency (Al-Adawi, Powell, Greenwood, 1998), the participant is asked to verbally improvise as many different words as possible that begins with each of the three speci c letters relevant to Arabic Speakers as described elsewhere 33 . On this scale, lower scores denote a higher propensity to neuropsychological dysfunction.…”
Section: Neuropsychological Measuresmentioning
confidence: 99%
“…Verbal Fluency. In the Controlled Oral Word Association Test, or Verbal Fluency (Al-Adawi, Powell, Greenwood, 1998), the participant is asked to verbally improvise as many different words as possible that begins with each of the three speci c letters relevant to Arabic Speakers as described elsewhere 33 . On this scale, lower scores denote a higher propensity to neuropsychological dysfunction.…”
Section: Neuropsychological Measuresmentioning
confidence: 99%
“…The Buschke Selective Reminding Test was used to tap into immediate recall which represents working memory and attentional capacity [19]. The participants were read a list of 12 words and asked to recall as many as possible in a total of 3 trials.…”
Section: Sample Sizementioning
confidence: 99%
“…Cervo et al (2007) reported that more than 4 to 5 million people are affected with dementia in the United States. According to recent epidemiological studies more than 7 million in the USA alone are affected by dementia (Al-Adawi et al, 2014). According to Al-Adawi et al, by the year 2047, the incidence of Alzheimer's dementia is projected to affect 8.64 million American people.…”
Section: Prevalence Of Dementia Pain and Agitationmentioning
confidence: 99%